EMERGENCY CARE FOR PATIENTS WITH ACUTE CORONARY SYNDROME IN EMERGENCY CARE - G.T.Madjidova; G.I. Sunnatova; A. Mardiev; A.Suynov (Journal Park Publishing, 2023)
Cardiovascular disease is one of the leading causes of death and disability in the world, with acute coronary syndrome (ARD) being the leading cause of death. Acute coronary syndrome (ACS) is an acute coronary insufficiency based on all clinical manifestations, which usually develops against the background of atherosclerosis of the coronary arteries. Some features of the pathogenesis and clinical features of OCD predetermine the most important organizational principles, methods of diagnosis and treatment. , in which time and the chosen treatment algorithm are very important, determining the prognosis of the disease and the subsequent life of the patient.